INCIDENCE, OUTCOME AND RISK FACTORS FOR SEPSIS - A TWO YEAR RETROSPECTIVE STUDY AT SURGICAL INTENSIVE CARE UNIT OF A TEACHING HOSPITAL IN PAKISTAN - Asghar, Ali; Hashmi, Madiha; Rashid, Saima; Khan, Fazal Hameed (Journal of Ayub Medical College Abbottabad, 2016)
Background: Sepsis is amongst the leading causes of admission to the intensive care units and is associated with a high mortality. However, data from developing countries is scarse. Aim of conducting this study was to determine the incidence, outcome and risk factors for sepsis on admission to surgical intensive care unit (SICU) of a teaching hospital in Pakistan. Methods: Two year retrospective observational study included all consecutive adult admissions to the surgical intensive care unit (SICU) of a University Hospital, from January 2012 to December 2013. Results: Two hundred and twenty-nine patients met the inclusion criteria. Average age of the patients was 46.35±18.23 years (16-85), mean Acute Physiology and Chronic Health Evaluation II (APACHE II) score was 15.92±8.13 and males were 67.6%. Median length of ICU stay was 4 [IQR 5]. 43% patients fulfilled the criteria of sepsis at the time of admission to the SICU and incidence of severe sepsis/septic shock was 35%. Abdominal sepsis was the most frequent source of infection (57.5%). The overall intensive care unit mortality was 32.31% but the mortality of sepsis-group was 51.15% as compared to 17.7% of the non-sepsis group. Stepwise logistic regression model showed that increasing age, female gender, non-operative admission, admission under general surgery and co-morbidities like ischaemic heart disease and chronic kidney disease were significant predictors of sepsis. Conclusion: The incidence of sepsis and severe sepsis/septic shock, on admission to SICU is high and mortality of the sepsis group is nearly three times the mortality of the non-sepsis group.